2022
DOI: 10.3389/fsurg.2022.995949
|View full text |Cite
|
Sign up to set email alerts
|

Progress in screening strategies for neonatal developmental dysplasia of the hip

Abstract: Developmental dysplasia of the hip (DDH) is the most common congenital disease of the musculoskeletal system in newborns and encompasses a disease spectrum ranging from a stable hip with a mildly dysplastic acetabulum to complete hip dislocation. Systematic screening for infant DDH has been performed for several decades all over the world and has contributed greatly to the early detection, diagnosis and treatment of DDH. However, some cases of delayed diagnosis still occur among the screened population, or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
0
9
0
10
Order By: Relevance
“…There were 15 Severin group Ia (46.8%), 1 Severin group Ib (3.1%), 8 Severin group IIa (25%), 2 Severin group IIb (6.2%), 4 Severin group III (12.5%), and 2 Severin group IVa (6.2%) hips. No hips were rated as Severin group V or VI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 15 Severin group Ia (46.8%), 1 Severin group Ib (3.1%), 8 Severin group IIa (25%), 2 Severin group IIb (6.2%), 4 Severin group III (12.5%), and 2 Severin group IVa (6.2%) hips. No hips were rated as Severin group V or VI.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 As the introduction of clinical and ultrasound screening programs allowed earlier treatment, the frequency of surgical treatment in DDH is gradually decreasing. 3,4 However, studies with long-term follow-up showed that a substantial number of hips develop osteoarthritis earlier than expected, even in well-treated hips. 2,[5][6][7] This highlights the importance of studies with even longer-term follow-up.…”
mentioning
confidence: 99%
“…A 2022 systematic review that excluded non-English language papers also concluded that the rate of late detected DDH, defined as greater than 12 weeks of age, and surgical treatment were not significantly different among different screening strategies 38. Conversely, two systematic reviews both supported universal ultrasound, with one showing favourable results of universal ultrasound in five out of six studies and concluding that universal ultrasound screening is cost effective 3940. A recent systematic review also concluded that universal screening shows a trend towards lower prevalence of late DDH but with increased bracing and without a reduction in surgical procedures 41.…”
Section: Why Is Ddh Missed?mentioning
confidence: 99%
“…The Pavlik harness appears to be the most used brace ( 7 ). According to medical literature, despite the current debate between selective and universal screening ( 8 10 ), hip ultrasound is considered the most reliable diagnostic examination for DDH ( 11 , 12 ). Until now, available literature ( 13 15 ) did not recommend (even in children with risk factors, including breech presentation) further follow-up after a negative hip ultrasound examination.…”
Section: Introductionmentioning
confidence: 99%